Peran Program Keluarga Harapan (PKH) dalam Meningkatkan Kesejahteraan Masyarakat Desa Balesono Kecamatan Ngunut Kabupaten Tulungagung - Salma Nailin Naja; Abdul Roziq Asrori (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The Family Hope Program (PKH) experiences a phenomenon, such as the status of the beneficiary community is more due to the encouragement of consumerism. Thus, the beneficiary community must really utilize the assistance of the Family Hope Program (PKH) as well as possible, to improve their quality of life and welfare so that the beneficiary community does not lose assistance from the Family Hope Program (PKH). Research Location, in Balesono Village, Ngunut District, Tulungagung Regency, East Java. The purpose of this research is to describe and analyze the utilization of PKH funds by PKH participants in improving welfare including the participation of PKH participants in participating in the PKH work program. The research approach used in this research uses descriptive qualitative. Data were collected using in-depth interview techniques, observation and documentation studies. Infromants were selected purposively based on criteria relevant to the research objectives. The results of this study show that PKH has a significant role in improving the welfare of the Balesono Village community, this role includes improving the quality of education, PKH helps beneficiaries to send their children to school with tuition assistance, increased access to health services The Family Hope Program (PKH) helps beneficiaries to get health services by providing health fee assistance, improving the quality of life, the Family Hope Program (PKH) helps improve the quality of life of the community through routine socialization once a month, the community has carried out their rights and obligations as beneficiaries of assistance, and assistants and related parties also provide guidance to beneficiaries to utilize assistance to improve their welfare. It is hoped that related parties for the next year will upgrade data collection so that PKH assistance funds are properly utilized. Researchers also recommend that future researchers need to examine more deeply the increasing synergy between institutions, namely village officials and assistants in the implementation of the Family Hope Program (PKH) in Balesono village.